2013
DOI: 10.1111/ejh.12070
|View full text |Cite
|
Sign up to set email alerts
|

Weekly intravenous bortezomib is effective and well tolerated in relapsed/refractory myeloma

Abstract: Weekly intravenous bortezomib when used in combination with steroids ± alkylator is effective in relapsed/refractory MM, producing outcomes comparable with biweekly regimens and with lower rates of peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…dara 16 mg/m2 + bor1.3 mg/m2 + dex20 mg25118.56421.8432. bor1.3 mg/m2 + dex20 mg2477.2Observational trials Avet-Loiseau et al [40]dex40mg + len25mg2079.66531.744 Chang et al [41]bor1.3 mg/m2659.554> = 21.331 Fukushima et al [72]bor1.3 mg/m2 + dex20mg2216.86922.141 Hou et al [73]dex20/40 mg + len25mg1998.36042.847 Kneppers et al [42]dex40mg + len25mg11710613.52.737 Lacy et al [74]dex40mg + pom2mg344.86241.732 Moore et al [43]bor1.3 mg/m252137212.640 Oehrlein et al [75]Dex < 160-480 mg2611.67122.854Len10-25 mg Pantani et al [76]bor1.3 mg/m2 + dex20mg858.75822.440 Richardson et al [77]bor1.3 mg/m2 + dex40mg + pan20mg555.46141.947 Terpos et al [78]dex40mg + thal200mg3586322.234 Walter-Croneck et al [44]bor1.3 mg/m2708146012.155 bev bevacizumab, bor bortezomib, carf carfilzomib, cyc cyclophosphamide, dara daratumumab, dex dexamethasone, elo elozum...…”
Section: Resultsmentioning
confidence: 99%
“…dara 16 mg/m2 + bor1.3 mg/m2 + dex20 mg25118.56421.8432. bor1.3 mg/m2 + dex20 mg2477.2Observational trials Avet-Loiseau et al [40]dex40mg + len25mg2079.66531.744 Chang et al [41]bor1.3 mg/m2659.554> = 21.331 Fukushima et al [72]bor1.3 mg/m2 + dex20mg2216.86922.141 Hou et al [73]dex20/40 mg + len25mg1998.36042.847 Kneppers et al [42]dex40mg + len25mg11710613.52.737 Lacy et al [74]dex40mg + pom2mg344.86241.732 Moore et al [43]bor1.3 mg/m252137212.640 Oehrlein et al [75]Dex < 160-480 mg2611.67122.854Len10-25 mg Pantani et al [76]bor1.3 mg/m2 + dex20mg858.75822.440 Richardson et al [77]bor1.3 mg/m2 + dex40mg + pan20mg555.46141.947 Terpos et al [78]dex40mg + thal200mg3586322.234 Walter-Croneck et al [44]bor1.3 mg/m2708146012.155 bev bevacizumab, bor bortezomib, carf carfilzomib, cyc cyclophosphamide, dara daratumumab, dex dexamethasone, elo elozum...…”
Section: Resultsmentioning
confidence: 99%
“…Our observed rate of treatment emergent PN was also higher than that reported in either the SUMMIT [3] or CREST [4] trials. Newer methods of bortezomib dosing, such as subcutaneous or weekly administrations, appear to significantly lower the rate of PN, but it remains an important issue [11, 12, 35]. These modifications would seem the current best approach in minimizing bortezomib-related PN as the preliminary data from our small study does not support any advantage for the inclusion of ALCAR in this clinical setting.…”
Section: Discussionmentioning
confidence: 92%
“…In conclusion, treatment with scBor demonstrated a lower incidence and severity of PN compared with ivBor administration, but did not adversely affect the efficacy of treatment when combined with thalidomide and dexamethasone. Previous studies have indicated that a weekly dose of bortezomib should be used within combinatorial treatments in order to achieve the lowest PN rates (26)(27)(28). However, the most efficient dose schedule of bortezomib under varying ISS stages and patient demographics requires additional research.…”
Section: Discussionmentioning
confidence: 99%